The Mechanics of Social Interactions Between Cats and Their Owners - Turner, Dennis C. (Frontiers in Veterinary Science, 2021)
This review summarizes what is known from ethological studies of interactions between cats and humans in both colonies and the home setting. Only results from data that have been properly analyzed and published are included. Some observational data have been juxtaposed to assessments of the animals’ character and owner personality traits. All interactions between cats and humans discussed here assume that the animals were socialized to people as kittens. Even though early socialization is important, other factors have been shown to affect the establishment of cat-human relationships. Optical and acoustic behavioral elements used to communicate with other cats can be perceived by people and are employed by the cats when interacting with them. Humans have added behavioral elements to their social repertoire when interacting with their cats. The initiation, and the initiator of interactions between cats and humans influence both duration of interaction and total interaction time in the relationship. Compliance with the interactional “wishes” of the partner is positively correlated between cats and humans over all human-cat dyads examined. Cats do not spontaneously prefer one gender or age cohort of people, but the humans in those cohorts behave differently to the cats causing the latter to react differentially. The dyadic interaction structure has also been shown to differ between women and men and between older and younger adults. Purebred and non-purebred cats have also been compared. Cats – both their presence and their behavior – can affect human moods and human mood differences affect the behavior of the cats.